Reduction in energy consumption and CO2 emissions by retrofitting an existing building to a net zero energy building for the implementation of SDGs 7 and 13 - Razzaq, Ibtisam; Amjad, Muhammad; Qamar, Adnan; Asim, Muhammad; Ishfaq, Kashif; Razzaq, Afia; Mawra, Khadija (Frontiers in Environmental Science, 2023)
This work aims to reduce the energy consumption in existing buildings by retrofitting and converting them into net zero energy buildings (NZEB). Various retrofits for an existing academic building were modelled and analyzed using REVIT software. Energy consumption was reduced to approximately 34% through retrofits, and a solar system of 41.6 kW was integrated to meet the reduced energy demand, consequently converting the building into an NZEB. Furthermore, environmental and economic analyses were conducted, and the results show a reduction of 32.8 metric tons of CO2 emission per year as a result of retrofitting the building to NZEB. The retrofits in building envelope and electrical appliances have a payback period of 2.96 and 2.62 years, respectively. Whereas the proposed solar system has a payback period of 2.3 years only. Moreover, the building was rated through the LEED rating tool, and it qualifies for silver certification after retrofits and integration of renewable energy sources (RES). The reduction in energy consumption and integration of renewable energy sources contribute to achieve SDG 7, and reduced CO2 emissions save climate variations which lead to achieve SDG 13.